Effect of Supplementing Molasses Based Multi-Nutrient Liquid Supplement (MMLS) on Nutrient Intake, Digestibility and Growth Performance of Buffalo Calves - Yengkhom, Rojita; Singh, Putan; Verma, A K; Handique, Bornalee (Indian Journal of Animal Nutrition, 2020)
Twenty-one buffalo calves (111Â±4.53 kg BW, 6-8 months age) were assigned to 3 groups (T1, T2 and T3) consisting of 7 animals each in a completely randomized block design. Concentrate mixture composition was remained the same for all three groups; however, concentrate to wheat straw ratio were 60:40, 50:50 and 40:60 in groups in T1, T2 and T3, respectively. Additional molasses based multi-nutrient liquid supplement (MMLS) was provided in T2 and T3 groups @ 5% and 10% DMI respectively. Daily intake of green oats, dry matter (DM), OM, NDF and ADF did not differ significantly (P>0.05) among groups. However, concentrates and EE intake were significantly (P<0.01) higher in calves of T1 group followed by T2 and T3. Wheat straw (kg/d), CP (kg/d, kg/d W0.75) and DCP (kg/d, kg/d W0.75) intake were significantly (P<0.01, P<0.05) higher in MMLS treated groups when compared to control. The digestibility coefficient of DM, OM, CP, EE, NDF and ADF did not differ significantly among groups. Initial and final body weight, total weight gain, ADG, DMI and FCR were also comparable (P>0.05) among the groups. Reducing the amount of concentrate and replacing the reduced amount by MMLS @5% and 10%, depending on the concentrate to roughage ratio can increase the ADG and thus growth rate of buffalo calves without any adverse effects on DMI and digestibility of nutrients.